2020
DOI: 10.3906/kim-2007-67
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidant capacities and antioxidant components of commercial bitter melon (Momordicacharantia L.) products

Abstract: In this study, the total phenolic contents and total antioxidant capacities of some commercial bitter melon products (powder, packaged powder, capsule, paste in olive oil), and of unripe and ripe fruits were determined by spectrophotometric and chromatographic methods. The total antioxidant capacities of unripe and ripe bitter melon samples, determined by CUPRAC (Cupric Reducing Antioxidant Capacity Assay) and ABTS (2,2′-Azinobis-(3-Ethylbenzthiazolin-6-Sulfonic Acid)/HRP (Horseradish peroxidase) methods, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The inhibitory impacts of BME on HAA generation might be ascribed to the total antioxidant capacity and phenolic content of the extract, which were measured as 150.8 ± 24.33 mmol TE/kg and 35035.71 ± 893 mg GAE/kg, respectively. Consistent with the current results, previous research also demonstrated that BME exhibited a high antioxidant capacity and phenolic content (Akyuz et al, 2020;Lee et al, 2017;Tan et al, 2014). For instance, the total phenolic content and antioxidant capacity of aqueous and ethanolic BME were measured as 10.6 ± 0.2 mg GAE/g dw and 94.8 ± 1.3 μmol TE/g, and 10.7 ± 0.3 mg GAE/g dw and 95.7 ± 3.5 μmol TE/g, respectively (Tan et al, 2014).…”
Section: Ctsupporting
confidence: 92%
“…The inhibitory impacts of BME on HAA generation might be ascribed to the total antioxidant capacity and phenolic content of the extract, which were measured as 150.8 ± 24.33 mmol TE/kg and 35035.71 ± 893 mg GAE/kg, respectively. Consistent with the current results, previous research also demonstrated that BME exhibited a high antioxidant capacity and phenolic content (Akyuz et al, 2020;Lee et al, 2017;Tan et al, 2014). For instance, the total phenolic content and antioxidant capacity of aqueous and ethanolic BME were measured as 10.6 ± 0.2 mg GAE/g dw and 94.8 ± 1.3 μmol TE/g, and 10.7 ± 0.3 mg GAE/g dw and 95.7 ± 3.5 μmol TE/g, respectively (Tan et al, 2014).…”
Section: Ctsupporting
confidence: 92%
“…An orally administered olive oil extract of Momordica charantia L. at a dose of 330 mg/kg lowered the ulcer index by 95% fifteen minutes before the production of a gastric ulcer, while an ethanol extract at a dose of 310 mg/kg only reduced the ulcer index by 56% [34]. The methanolic extract at 100 mg/kg, on the other hand, resulted in a 61% reduction in ulcer index [35]. Hexane extracts of Combretum duarteanum Cambess leaf and Dodonaea viscosa also performed better than the ethanolic or water extracts [36].…”
Section: Literature Searchmentioning
confidence: 96%
“…The contents of vanillic acid (0.87 µg/mg), catechin (0.30 µug/mg), and coumaric acid (0.01 µg/mg) were also found in aqueous extracts of M. charantia fruit residues. [39] Akyüz et al [40] also proved that the presence of phenolic compounds of catechin, rutin, gallic acid, quercetin, vanillic acid, gentisic acid, chlorogenic acid, epicatechin, syringic acid, p-coumaric acid and benzoic acid in the M. charantia fruit are the major contributors for the antioxidant property. Vikneswari et al [26] reported that margaric acid, ascorbic acid, quercetin-3-glycosides, brevifolincarboxylic acid, Augustin H, goya glycoside G and cucurbitacin E 3-Malonylmomordicin I were found in the M. charantia fruit which was analyzed by LC-MS-QTOF.…”
Section: Identification and Quantification Of Phenolic Compoundsmentioning
confidence: 96%